Molecule to Supramolecule: Effect of Assembly on the Molecular Properties of H-bonded Chiral Assembly of Coordination Complexes with Amino Acid Derivatives - Dubey, Mrigendra (My University, 2011)
Metal complexes of amino acid derived reduced Schiff base ligands generated several interesting architectures including chiral capsule, channels and cavity owing to their flexibility, H-bonding ability, and inherent chirality.1,2 In this thesis, we have explored the chemistry of L-leucine derivative (Figure 1), and characterized a set of spontaneously formed crown ether analogue multinuclear assemblies, binding both cation and anion of a binary salt in the solid state. Considerable amount of work has been reported2 on the use of metal complexes as a crown ether/cryptand analogue,3 as well as anion receptor,4 but few molecular assemblies having both alkali metal ion and an anion binding site exist.5 Systematically changing the other part such as amino acid, metal Ni(II) or Cu(II) and alkali metal ions as well as counter anions, we have explored effects on multinuclear formation. Consequently, we have synthesized different type of monomers as well as their conversion towards multinuclear assembly in presence of alkali metal salts. Because of flexible nature of assembly towards Ni(II) and Cu(II) we got accomplishment in synthesis and characterization of mixed metal assembly which is challenging in the field of coordination chemistry. On changing alkali metal ion Na+/K+ to Cs+ monomer forms coordination polymer instead of multinuclear assembly. Apart from the coordination chemistry of leucine derivative, we have explored its gel formation properties by attaching hydrophobic pyrene moiety. To know the better understanding of gel formation, we have explored coordination chemistry of those gelators with Cu(II) and Zn(II) metal ions. Consequently, the complexes form void space within the lattice, and we were successfully inserted molecular iodine within the void space..
Ray, Manabendra
Keywords: CHEMISTRY